Plate VII. Burning of scrotum and penis by mustard gas. - Great Britain. Medical Research Committee (An Atlas of Gas Poisoning, 1918)
Drawing made on eleventh day.
Keywords: Gases, Asphyxiating and poisonous--Toxicology; Gases, Asphyxiating and poisonous--War use; Mustard gas